"There Are No Invalids in the USSR!" A Missing Soviet Chapter in the New Disability History - Sarah D. Phillips (Disability Studies Quarterly, 2009)
This article presents an overview of disability rights issues in the context of state socialism in the former Soviet Union, especially the Russian and Ukrainian Soviet Socialist Republics. The Soviet state’s governmentality of disability, and the little-known history of Soviet-era disability rights movements, produced important legacies that shape disability policy and discourses, rights movements, and experiences of disability in the region today. By focusing on Soviet approaches to housing, education, rehabilitation, and work vis-à-vis people with disabilities, and documenting the varied responses of disability communities, this article contributes a missing Soviet chapter to the new disability history. This approach encourages readers to reconsider some assumptions about the evolution of disability rights outside the West. Especially, I interweave discussions of Soviet-era state policy with descriptions of people’s personal experiences to emphasize the ways that people with disabilities in the former Soviet Union have been active agents–if not organized advocates–across the 20th century.